Assessing the role of peer education in improving clinical and patient-reported outcomes in adults with chronic kidney disease: A scoping review protocol - Anna Winterbottom; Jyoti Baharani; Hilary L. Bekker (PLoS ONE, 2026)
Purpose This paper describes a protocol for a scoping review examining the role of peer education programs for people with chronic kidney disease across diverse healthcare settings and cultural contexts. Method The protocol is guided by the Joanna Briggs Institute evidence synthesis guidance, and reported here following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for scoping reviews (PRISMA-P) guideline. Based on the population, intervention, comparator, and outcome (PICO) framework, our research questions are: 1) What models of peer education are used to supplement pre-treatment education in adults with chronic kidney disease? 2) What specific clinical and patient-reported outcomes are impacted by peer education in adults with chronic kidney disease? 3) What are the core components of peer education interventions for people with chronic kidney disease? 4) Are there variations in the need for, and experience of, peer education by patient characteristics (including ethnicity, socio-economic status, age, gender, disease stage)? The review process includes: 1) development of a comprehensive search strategy and inclusion criteria, developed iteratively with an information specialist to balance sensitivity (capturing all relevant studies) and specificity (minimizing irrelevant retrievals); 2) data extraction; 3) charting the data and quality assessment using the Mixed Methods Appraisal Tool (MMAT) for diverse study designs and the Joanna Briggs Institute (JBI) critical appraisal checklists for specific and 4) data synthesis and analysis. A data extraction form will elicit identical information from each study meeting the inclusion criteria. Data analysis will be determined by findings, and is likely to include quantitative summaries organized by outcome categories (clinical outcomes, patient-reported outcomes, decision-making quality) and narrative synthesis. Where heterogeneity precludes meta-analysis, findings will be synthesized descriptively using tables and narrative summary. Conclusion This scoping review will synthesize current evidence from diverse international healthcare contexts, and identify research gaps, to provide guidance for services on defining, developing and implementing peer education interventions that meet the needs of people with chronic kidney disease globally, with attention to contextual factors that may influence transferability across healthcare systems.